Multi-scale Calibration and Validation of MHYDAS-Erosion for A Small Mediterranean Vineyard Catchment: A Case Study - Gumiere, Silvio; Delattre, Laurence; Le Bissonnais, Yves; Cheviron, Bruno; Ben Slimane, Abir; Raclot, Damien (Revue des sciences de l’eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2014)
AbstractIn this work we present a case study of the multi-scale calibration and validation of MHYDAS-Erosion applied to a Mediterranean vineyard. The calibration was performed using expert knowledge in linking physical parameters to land uses with the automatic parameter estimation software PEST. MHYDAS-Erosion was calibrated and validated using spatially distributed observations on total discharge and soil loss. Calibration has been performed within six rainfall events; both hydrological and erosion parameters were calibrated using RMSE, R2 and the modified version of the Nash-Sutcliffe model efficiency criteria. Calibration results indicate there was good agreement between simulated and observed total discharge and total soil loss at the seven observation points (modified Nash-Sutcliffe efficiency (mNSE) ranging between 0.89 and 0.95). Acceptable results were obtained in terms of parameter values, identification of their physical meaning and coherence. However, some limitations were also identified, and could be remedied in more detailed studies involving (i) spatially-distributed rainfall on the catchment, (ii) a description of groundwater exfiltration and (iii) spatially-distributed properties of the ditches over the catchment. Validation results were quite satisfactory for three of the four validation events. The results from this case study suggest that MHYDAS-Erosion may need a specific calibration when applied to another catchment, but once it is calibrated, it could be used for multi-scale soil loss forecasting.